(untitled) (Conferencea, 2023)
The article presents an overview of the literature on one of the important problems of modern health care — obesity in children and adolescents. The consequences of obesity in childhood are described in detail. Obesity among children and adolescents in the modern world is one of the most important problems for residents of most countries of the world.